2019
DOI: 10.1002/chem.201902351
|View full text |Cite
|
Sign up to set email alerts
|

Origins of Enantiopreference of Mycobacterium smegmatis Acyl Transferase: A Computational Analysis

Abstract: Acyl transferase from Mycobacterium smegmatis (MsAcT) is a promising biocatalyst because it catalyzes an acyl transfer reaction in aqueous solution, thereby accepting many primary and secondary alcohols as substrates. MsAcT also exhibits high enantioselectivity for a selected number of secondary alcohols. To increase the applicability of this enzyme for the production of optically active compounds, a detailed understanding of the reaction mechanism and the factors that affect enantioselectivity is essential. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 42 publications
2
34
2
Order By: Relevance
“…15,36 Additionally, sites suggested by computational studies to be relevant to acyltransferase activity were investigated. 35,37 Binding Site and Tunnel Analyses. Residues forming the active site of MsAcT (PDB code: 2Q0Q) were examined.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15,36 Additionally, sites suggested by computational studies to be relevant to acyltransferase activity were investigated. 35,37 Binding Site and Tunnel Analyses. Residues forming the active site of MsAcT (PDB code: 2Q0Q) were examined.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Another recently published computational study suggested that W16, A55, F150, and F154 are important in determining the enantioselectivity of MsAcT. 37 This hypothesis was based on differences in the stabilizing effects these residues have on transition states, depending on the substrate enantiomer used. Because of their roles in stabilization of transition states, these residues probably also influence acyl transfer efficiency and are therefore potential hotspots for improving the AT:H ratio and enantioselectivity of MsAcT.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extensive literature of esterases reveals many important mechanistic details, but no information on the chirality of the respective oxyanions is explicitly discussed. 14,18,113,114 The literature on the mechanism of proteases is even more vast, and the chirality of oxyanions has also been routinely ignored. Here, we mention only a single example case.…”
Section: Selected Case Studiesmentioning
confidence: 99%
“…The extensive literature of esterases reveals many important mechanistic details, but no information on the chirality of the respective oxyanions is explicitly discussed. ,,, …”
Section: Selected Case Studiesmentioning
confidence: 99%